1984
DOI: 10.1016/0378-1135(84)90046-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral immunization on the population of lymphocytes migrating to the mammary gland of the sow

Abstract: Kortbeek-Jacobs, J.M.C., van Kooten, P.J.S., van der Donk, J.A., van Dijk, J.E. and Rutten, V.P., 1984. The effect of oral immunization on the population of lymphocytes migrating to the mammary gland of the sow. Vet. Microbiol., 9: 287--299.Sows were immunized orally with live Escherichia coli according to various immunization schedules. Six pregnant gilts were used; 4 immunized at various intervals during the last month of gestation, 1 control immunized after parturition following suppression of lactation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Vaccination or natural immunization of the pregnant cow, ewe or sow against enterotoxigenic Escherichia coli [38,39,40] or intestinal viruses [41,42], can provide a degree of protection for the newborn. As an example, while only limited protection against viral challenge occurred in calves fed once shortly after birth with a pooled colostrum from cows immunized against bovine rotavirus, a shorter duration of diarrhea was observed [43].…”
Section: Immune Milkmentioning
confidence: 99%
“…Vaccination or natural immunization of the pregnant cow, ewe or sow against enterotoxigenic Escherichia coli [38,39,40] or intestinal viruses [41,42], can provide a degree of protection for the newborn. As an example, while only limited protection against viral challenge occurred in calves fed once shortly after birth with a pooled colostrum from cows immunized against bovine rotavirus, a shorter duration of diarrhea was observed [43].…”
Section: Immune Milkmentioning
confidence: 99%
“…It is well documented that immunization of pregnant animals provides passive protection to suckling neonates against bacterial and viral infections Bohl and Saif, 1975;Bohl et al, 1974;Kortbeek-Jacobs et al, 1984;Lanza et al, 1995;Moon and Bunn, 1993;Saif et al, 1972;Saif and Fernandez, 1996;Saif et al, 1984;Wilson et al, 1972). Lactogenic immunity is described as the continuous supply of passively acquired immunoglobulins (IgG, IgM and sIgA) through the ingestion of colostrum and milk, but with IgG being the dominant isotype in colostrum and sIgA in milk (Klobasa et al, 1987).…”
Section: Homing Of Iga Plasmablasts From the Intestine To The Mammarymentioning
confidence: 99%
“…Like the respiratory tract, the mammary gland is part of the "integrated mucosal immune system". For instance, Kortbeek-Jacobs et al [37] demonstrated preferential accumulation of sensitised cells in the mammary gland after oral immunisation of sows with E. coli during lactation. This functionally important "entero-mammary link" mediates immunity of the offspring against antigens present in the maternal digestive tract [84].…”
Section: Mammary Glandmentioning
confidence: 99%